The right to privacy at work - Danilović Jelena (Anali Pravnog Fakulteta u Beogradu)
This paper discusses employees' right to privacy at work at the beginning of XXI century in Serbia and its relation to international regulations and practice. The right to privacy at work, in the context of this analysis, is considered as the right to protect employee's personal data from employer's improper intrusion. The first part of the paper provides overview of theories on privacy right as well as current data protection legal framework. This section shows that the concept of privacy changed significantly during the history and that development of data protection legislation, though intense, did not clarify some of the main ambiguities linked to this concept. Especially in Serbia, where data protection regulation is relatively new and practice rudimentary, there are many queries linked to the issue of privacy at work. The second part of the paper analyses in more details origins and importance of privacy legal standard established in the international practice - the 'reasonable expectations of privacy'. Understanding of this legal standard and especially its influence to recent court practice of the European Court of Human Rights is important for comprehension of employee's right to privacy. In-depth analysis shows that this standard includes an external element (privacy expected by the society) and internal element (privacy expected within the specific employer). While there are conceptual differences between the USA and European practice, the internal element of this legal standard in both cases has a major influence in the employment privacy disputes. Finally, the paper proposes that enacting of internal privacy policies, with full respect of data protection regulations, could provide for viable reasonable expectations of privacy at work. This may eventually lead to easier distinction of the fine line between employee's privacy and employer's interests.